2015
DOI: 10.1039/c4lc01048e
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of pneumatic digital logic circuits

Abstract: The scaling of integrated circuits to smaller dimensions is critical for achieving increased system complexity and speed. Digital logic circuits composed of pneumatic microfluidic components have to this point been limited to a circuit density of 2-4 gates cm(-2), constraining the complexity of the digital systems that can be achieved. We explored the use of precision machining techniques to reduce the size of pneumatic valves and resistors, and to achieve more accurate and efficient placement of ports and via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 11 publications
(30 reference statements)
0
47
0
Order By: Relevance
“…2017, 2, 1600188 www.advmattechnol.de www.advancedsciencenews.com TARGE169 and CONTA171 were used. No rough cutting for planarizing purposes was necessary as seen in other work; [30] the stock Figure 7. Preliminary simulations showed that the smallest gap between the pillar and pads enabled the highest contact area.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2017, 2, 1600188 www.advmattechnol.de www.advancedsciencenews.com TARGE169 and CONTA171 were used. No rough cutting for planarizing purposes was necessary as seen in other work; [30] the stock Figure 7. Preliminary simulations showed that the smallest gap between the pillar and pads enabled the highest contact area.…”
Section: Methodsmentioning
confidence: 99%
“…NC instructions were coded in Tool Path Language, and generated using CAMotics 1.0.0. No rough cutting for planarizing purposes was necessary as seen in other work; [30] the stock Technol. 2017, 2, 1600188 www.advmattechnol.de www.advancedsciencenews.com was sufficiently planar as received.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duncan et al used precision machining techniques to build a variety of digital logic circuits using fluidics [20]. The used a computer numerically controlled (CNC) machine to make normally closed pneumatic membrane valves from Grover and Jensen [13], [21] and demonstrated an operating T flipflop.…”
Section: A Literaturementioning
confidence: 99%
“…This mixture was then degassed in a vacuum desiccator. Additional bonding strength was achieved through the use of office binder clips 28 . The via on the control layer, shown in Figure 3, is accessed through holes punched in the PDMS membrane.…”
Section: Microfluidic Materials and Assemblymentioning
confidence: 99%